IMPROVEMENT IN THE DIAGNOSIS OF CHRONIC PERIODONTITIS IN CHILDREN (World Bulletin of Social Sciences, 2024)
The clinical development of periodontitis in children differs significantly from the similar pathological process in adults. This distinction arises due to the occurrence of these processes in morphologically and functionally immature tissues, which can exhibit an inadequate response to causal factors.As a result, children are more prone to developing severe forms of periodontitis compared to adults, despite the overall lower prevalence of destructive periodontitis. In fact, chronic periodontitis is responsible for acute inflammatory processes of the maxillofacial region (such as abscess, phlegmon, and lymphadenitis) in 85-98% of cases, and it can also contribute to systemic and other dental diseases.
Keywords: Incidence and discriminant; models of chronic periodontitis; children